Techniques using ImageJ for histomorphometric studies (Research, Society and Development, 2020)
Computational histomorphometry is an available and easy tool that has been used in the assessment of morphophysiological tissue changes, offering greater scientific reliability to the data, as well as facilitating the automation process. The present work aimed to describe the application of the methodology of the free software ImageJ for morphological evaluation of fish tissues. For this, micrographs of histological sections of the intestinal tract of fish stained with Periodic Acid-Schiff (PAS) were used as a model. The images were analyzed for variables of length, width, and tissue area and, number of cells or molecules. The application of computational histomorphometry demonstrated efficiency in the evaluation of histological structures of the intestine of fish supplemented with probiotics, contributing to the improvement of image analysis techniques in animal tissue models.